MAGNETIC RESONANCE IMAGE AND CROSS SECTIONAL ANATOMY OF THENORMAL BRAIN OF GOAT (CAPRA HIRCUS) - Kassab, A. (Emirates Journal of Food and Agriculture, 2017)
Among ruminant animals, there are few studies on the brain of the goat (Capra hircus). Our study demonstrates the first series of magnetic resonance (MR) imaging-based anatomically labeled sectioned images of the brain of the goat. T2-weighted dorsal MR images were acquired with a 1.5-T Philips NT scanner with slice spacing of 4 mm thickness. Frozen cross-sectional slices of goat brain were photographed and compared with the MR images. The cerebral hemispheres, hippocampus, thalamus, hypothalamus, cerebellum, pons, myelencephalon and other major features of the brain are clearly defined in the images. These MR images provide an excellent soft tissue contrast and anatomic details of the brain of the goat. MR imaging provides a mean for consistent evaluation of the goat brain structures that could be useful for evaluation of diseases that affect the brain region.